Eine bisher unbekannte Larve der Gattung Quedius Steph. aus Nestern von Microtus arvalis Pallas (Coleoptera: Staphylinidae). - Smetana, Aleš (Contributions to Entomology = Beiträge zur Entomologie, 1957)
The author describes the hitherto unknown larva of Quedius vexans Eppelsh. The larvae were found in nests of the vole Microtus arvalis Pallas. There are added some bionomic notes as like as some informations about two species of parasitic Hymenoptera, Codrus ligatus Nees and Codrus brevicornis (Haliday) (Proctotrupoidea: Proctotrupidae), reared from larvae of Quedius vexans.